2004
DOI: 10.1093/nar/gkh783
|View full text |Cite
|
Sign up to set email alerts
|

Portrait of transcriptional responses to ultraviolet and ionizing radiation in human cells

Abstract: To understand the human response to DNA damage, we used microarrays to measure transcriptional responses of 10 000 genes to ionizing radiation (IR) and ultraviolet radiation (UV). To identify bona fide responses, we used cell lines from 15 individuals and a rigorous statistical method, Significance Analysis of Microarrays (SAM). By exploring how sample number affects SAM, we rendered a portrait of the human damage response with a degree of accuracy unmatched by previous studies. By showing how SAM can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
129
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(145 citation statements)
references
References 48 publications
(59 reference statements)
13
129
2
Order By: Relevance
“…This immediate transcriptional response to gamma irradiation is governed by ATM, but not by ATR (Culligan et al, 2006). In contrast to the robust transcriptional response in A. thaliana, microarray studies in human cells show that the magnitude of the change in the expression of irradiation-responsive genes is not as great (Rieger and Chu, 2004). Furthermore, few DNA repair genes are transcriptionally induced by gamma irradiation in human cells.…”
Section: The Dna Damage Response In a Thalianamentioning
confidence: 86%
“…This immediate transcriptional response to gamma irradiation is governed by ATM, but not by ATR (Culligan et al, 2006). In contrast to the robust transcriptional response in A. thaliana, microarray studies in human cells show that the magnitude of the change in the expression of irradiation-responsive genes is not as great (Rieger and Chu, 2004). Furthermore, few DNA repair genes are transcriptionally induced by gamma irradiation in human cells.…”
Section: The Dna Damage Response In a Thalianamentioning
confidence: 86%
“…Many of these genes are known oncogenes. Our low-dose gene set included a strong apoptosis-associated gene, TNF receptor form 6 (TNFRSF6), that was previously associated with high-dose transcript response [20,72] for differing qualities of ionizing radiation [53]. Interestingly, we also identified two low-dose responsive genes thought to be associated with anti-apoptotic functions: CD83 and PTMA.…”
Section: Low-dose Functions and Network Associated With Membranes Omentioning
confidence: 99%
“…High-dose exposures (>2 Gy) are known to modulate the expression of genes associated with genotoxic and physiological stress responses including DNA damage sensing and repair, and immune response [11][12][13][14][15][16][17][18][19][20][21]. After high doses, the cellular decisions to initiate rescue or cell death appear to be mediated by signaling pathways and secondary messengers [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of human lymphoblastoid cell lines from healthy adults, for example, Chu and colleagues found that thousands of mRNAs were up or downregulated after cells were exposed to ionizing radiation (IR) or ultraviolet light. 3 Similarly, as much as 20% of the genes in budding yeast showed a two-fold or greater change in mRNA levels in response to MMS treatment or ionizing radiation. 4 However, it would seem intuitively obvious that the last thing one would expect cells to do shortly after incurring significant DNA damage is to start transcribing new genes.…”
Section: Post-transcriptional Control Of Gene Expression Is Essentialmentioning
confidence: 99%